Pengaruh Konsumsi Buah Pisang Ambon (Musa Paradisiaca) Terhadap Emesis Gravidarum pada Ibu Hamil Trimester I - Nurwirani; Winarna, Nuristy Brillian Ainindyahsari; Hariadji Sugito (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKes Banyuwangi, 2025)
Emesis gravidarum, which refers to nausea and vomiting in early pregnancy, is believed to arise due to fluctuations in the endocrine system. A non-pharmacological intervention is the consumption of Ambon banana, which contains vitamin B6 and folic acid. The purpose of this study was to assess the effect of banana consumption on emesis gravidarum in first trimester pregnant women. This study was conducted in 2023 at Sempu Health Center, Banyuwangi Regency. This study applies pre-experimental with one group pre and post design, the target population consists of all first trimester pregnant women who experience nausea and vomiting at Sempu Health Center. A total of 30 people were selected as samples using consecutive sampling technique and data collection on the frequency of nausea and vomiting in mothers using the PUQE (Pregnancy Unique Quantification of Emesis) questionnaire. The intervention was 200 grams of Ambon banana, twice a day, for seven days. The results showed a decrease in the frequency of moderate emesis from 76.7% to 16.7% and an increase in mild emesis from 23.3% to 83.3% (p=0.001). Giving banana ambon demonstrated a statistically significant impact in reducing emesis gravidarum among first-trimester pregnant women.